Influence of fillers dense packing to the performance properties of water-dispersion coatings - Караваєв, Тарас Анатолійович (Eastern-European Journal of Enterprise Technologies, 2014)
The considerable attention of scientists and practitioners is devoted to improving of coatings performance properties. Providing the most fillers dense packing in the polymer matrix of paint coating is one way of development in this area. Purpose of the article is creating a fillers dense packing of performance properties of water-dispersion coatings. Object of study – the water-dispersion styrene-acrylic coatings filled by Ukrainian carbonates. Research of film tensile strength was carried out according to GOST 18299, resistance of coating to wet abrasion – according to ISO 11998. The mathematical model let to determine that the maximum packing of particles in the coating will be achieved when the ratio of carbonate filler for plastics (CFP, the average particle size 1.8 microns) to chalk grade MMC-1 (1.0 microns) as 85.4 wt.% to 14.6 wt. % respectively. The maximum films tensile strength (5.52 MPa) and coatings resistance to wet abrasion (4.8 micron thickness loss) got from water-dispersion paints achieved when filled by carbonates CFP and MMC-1 at ratio 85.0 wt.% and 15,0 wt.% respectively. This is higher than the corresponding values in the case of each of the fillers alone and at other ratios that confirmed of getting the most dense packing of the particles in the coating. The influence of fillers packing density to coating performance properties from the water-dispersion paints has been determined. Getting the most dense packing of particles at specified ratio of carbonate filler allows to improve the performance properties of water-dispersion coating through a uniform wetting of the filler particles by polymer, strengthening the adhesive bond between binder and filler. This is to promote the continuous phase, resistance to cracking and destruction of coatings.